Pelatihan Metode Balancing Statis Propeller Kapal Ikan pada Kelompok Nelayan di Kabupaten Pinrang - Nikmatullah, Muhammad Iqbal; Klara, Syerly; Muhammad, Andi Haris; Mahmuddin, Faisal; ., Rahimuddin; Hasan, Hasnawiyah; Hasbullah, Mansyur (Faculty of Engineering UNHAS, 2023)
The use of engine power in the ship propulsion system makes it easier for traditional fishermen to carry out their activities. On the other hand, modern technology requires basic knowledge to be operated and maintained properly and according to procedures. Incorrect installation of one machine component will of course have an impact on other components which will very detrimental to fishermen, as experienced by fishermen in Ammani Village, Pinrang Regency. The power transmission system from the propulsion engine to the ship's propeller via the shaft is an important component that must be considered. Sufficient understanding of this problem will have a very good impact on its use and service life. Selection and installation of an inappropriate transmission system will result in large vibrations, broken shafts, wear of bearings and clutches and can even damage the drive engine which is the most expensive component in the transmission system. In this activity, training was held on one of the problems often experienced by fishermen in Ammani Village, Pinrang Regency, namely propeller imbalance after undergoing a repair process. The series of activities consisted of presenting material about machinery transmission systems, propeller characteristics and propeller balancing demonstrations. Of the 20 (twenty) participants, there was an increase of 25% who answered understanding of power transmission systems, 20% increased in understanding of propeller characteristics and 45% increased in understanding of propeller static balancing methods after the activity was completed. By holding this activity, it is hoped that the fishermen participating in the training will understand and be able to carry out the static balancing process independently on the propeller before installing it. This will certainly provide a slight reduction in transmission system maintenance costs because the service life of the components is relatively longer.